Regret-sensitive treatment decisions - Yoichiro Fujii; Yusuke Osaki (Health Economics Review, 2018)
The threshold approach to medical decision-making, in which treatment decisions are made based on whether the probability of sickness exceeds a predetermined threshold, was introduced by (Pauker and Kassirer, N Engl J Med 293:229-234, 1975) and (Pauker and Kassirer, N Engl J Med 302:1109-1116, 1980). This study generalizes the threshold approach using regret theory. Regret theory is one of the established alternatives to expected utility theory (EUT), and partly overcomes the descriptive limitations of EUT. Under regret theory, agents suffer disutility from regret or enjoy utility from rejoicing by comparing the chosen alternative with the forgone one. We examine the effect of regret and rejoicing on the threshold approach by setting the EU case as a benchmark, and show conditions under which regret and rejoicing monotonically change the threshold probability. The threshold probability is lowered by regret and rejoicing under the reasonable condition in the sense that the condition can explain observed choices that EU fails to describe. This suggests that agents opt to undergo medical treatment by the feeling of regret and rejoicing. This result might explain the social problems that occur in relation to the public provision of medical services in many OECD countries such as medical expenditure rising faster than government forecasts. The results also imply that regret sensitivity might cause inequality of benefits from public medical services. Finally, we offer a solution to this problem.
Keywords: D81; I12; 330; Medical decision-making; Non-expected utility; Public medical service; Regret and rejoicing; Treatment threshold